The impact of sex and BMI on the clinical course of COPD and bronchial asthma - Wytrychowski, Krzysztof; Hans-Wytrychowska, Anna (Family Medicine & Primary Care Review, 2016)
Background. Bronchial asthma is a heterogeneous disease, and is one phenotype of asthma with obesity. Chronic obstructive pulmonary disease is the fourth most frequent cause of death in the world. Objectives. The aim of the study was to assess the influence of BMI and sex on the clinical course of uncontrolled asthma and COPD with moderate to severe airflow limitation. Material and methods . The study was performed on 2 groups. Group A: 72 adults suffering from asthma (38 F – females, 34 M – males) with at least 1 exacerbation requiring treatment with systemic corticosteroids in the year before the study. Group B: 79 patients (34 F, 45 M) with COPD Grades 2 and 3 according to GOLD. Data including age, gender, BMI, disease duration, treatment, concomitant diseases, pack-years, and number of exacerbations in the last year were collected. Asthma Control Questionnaire scores in group A and COPD Assessment Test scores in group B were collected. Pulmonary function tests were performed in both groups. Results . There were no differences between females and males in the analyzed variables in both groups. Obese patients (BMI > 30.0 kg/m2) were selected for analysis from group A (18 F, 10 M) and from group B (13 F, 16 M). In group A, the number of exacerbations was significantly lower in males (M 1.3 vs. F 1.9; p = 0.01). In group B the age of obese patients was higher than in patients with BMI ≤ 30.0 (68.3 vs. 62.5; p = 0.002). Conclusion . Poorer control of asthma in obese patients was associated with the female gender. Age is a risk factor for obesity development in patients with COPD.